Chinese traditional healing : the Berlin collections of manuscript volumes from the 16th through the early 20th century - Unschuld, Paul U. (Paul Ulrich), 1943- (Sir Henry Wellcome Asian series, 2012)
Research on past knowledge, practices, personnel and institutions of Chinese health care has focussed on printed text for many decades. The Berlin collections of handwritten Chinese volumes on health and healing from the past 400 years provide a hitherto unprecedented access to a wide range of data. They extend the reach of medical historiography beyond the literature written by and for a small social elite to the reality of health care as practiced by private households, lay healers, pharmacists, professional doctors, magicians, itinerant healers and others. The nearly 900 volumes surveyed here for the first time demonstrate the heterogeneity of Chinese traditional healing. They evidence the continuation of millennia-old therapeutic approaches long discarded by the elite, and they show continuous adaptation to more recent trends.